2019
DOI: 10.1111/nicc.12434
|View full text |Cite
|
Sign up to set email alerts
|

Supporting Muslim families before and after a death in neonatal and paediatric intensive care units

Abstract: Background: The death of a child is regarded as one of the most devastating events for a family. Families are reliant on nurses to not only provide end-of-life care but also to support and care for grieving families in a way that is sensitive to their cultural and religious needs and preferences.Aims: The aim of this study was to explore the perceived impact and influence of cultural diversity on how neonatal and paediatric intensive care nurses care for Muslim families before and after the death of infants/ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 38 publications
1
16
0
Order By: Relevance
“…Holy water recovered from the well of Zamzam in Mecca), Muslim rituals of body orientation towards Mecca after the baby dies and the use of cevs ¸en-muska (a small amulet with small prayers from the Quran) on the incubator. 36,37 In another study, families were concerned to minimize touching the body of the dead Muslim as much as possible by the health care providers if they are not of the same sex of the patient. 38 In the non-Muslim context, 39 nurses acknowledged that parents needed time to spend with critically ill baby and to be able to hope for a Divine intervention.…”
Section: Spiritual Needs Of Patients and Familiesmentioning
confidence: 99%
“…Holy water recovered from the well of Zamzam in Mecca), Muslim rituals of body orientation towards Mecca after the baby dies and the use of cevs ¸en-muska (a small amulet with small prayers from the Quran) on the incubator. 36,37 In another study, families were concerned to minimize touching the body of the dead Muslim as much as possible by the health care providers if they are not of the same sex of the patient. 38 In the non-Muslim context, 39 nurses acknowledged that parents needed time to spend with critically ill baby and to be able to hope for a Divine intervention.…”
Section: Spiritual Needs Of Patients and Familiesmentioning
confidence: 99%
“…According to the results of a qualitative study in Iran about caring for terminally ill patients, it is important to avoid harming them and respect their cultural and religious beliefs, as well as the patients’ and their families’ dignity ( 26 ). The results of a qualitative study in Saudi Arabia also showed that nurses working in NICUs had the experience of providing end-of-life care while respecting the neonates’ families, and that this respect remained the same even after the neonate’s death ( 18 ). According to the Islamic and cultural doctrine, family institution is considered vulnerable in Iran, and therefore the nurses in this study observed this and considered the families in caring for neonates.…”
Section: Discussionmentioning
confidence: 99%
“…This scale has been designed by Frommelt (1991) and used for terminally ill patients of any age ( 23 ). The scale consists of 30 items, 15 of which are expressed in a positive manner ( 1 , 2 , 4 , 10 , 12 , 16 , 17 , 19 , 20 , 21 , 22 , 23 , 24 , 26 , and 29 ) and emphasize the nurses’ attitudes toward the role of families in caring for terminally ill patients; the remaining 15 items are expressed in a negative manner ( 3 , 5 , 6 , 7 , 8 , 9 , 11 , 13 , 14 , 15 , 18 , 25 , 27 , 28 , and 30 ) and are related to the nurses’ fear and stress in caring for terminally ill patients. The items are scored based on the Likert scale (completely disagree, disagree, no idea, agree, and completely agree), and the overall scores range between 30 and 150.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These difficulties are even greater when the nurses providing the care were raised and trained in a different country, speak a different language and come from substantially diverse cultural and religious backgrounds. Against this backdrop, Al Mutair et al . conducted a descriptive qualitative study with interviews among non‐Muslim nurses working in paediatric and neonatal ICUs (NICU/PICU) in a large private hospital in Riyadh, Saudi Arabia who had cared for at least one infant or child who had died.…”
mentioning
confidence: 99%